Paradox of perception : the role of the second chair second violin in a symphony orchestra : a thesis presented in partial fulfilment of the requirements for the degree of Master of Management in Management at Massey University, Manawatu campus, New Zealand - Gilling, David Francis (Massey University, 2010)
The objective of this research thesis is to add to our understanding of work practices in the symphony orchestra and, in particular, to explore the functioning of the hierarchy which exists among the musicians of the orchestra (Koivunen, 2003; Marotto, Roos & Victor, 2007) As the literature regarding the orchestral organization is concerned primarily with relations between conductors and orchestras and, further, with the offstage implications of these interactions (Koivunen, 2003), I have focused instead on the onstage relationships among musicians that occur in the course of rehearsal, concert, and recording activity. In order to investigate these relations, I have undertaken a critical and reflexive study of the role of sub-principal (second chair) second violin in a full-time, fully professional symphony orchestra. In so doing I sought to interrogate my own experience through an autoethnographic methodology which is grounded in the phenomenology of Merleau-Ponty (2002) and draws on the sensemaking ideas of Weick (1995, 2001). The picture that emerged from this research was one of an embodied musician engaging in empathetic interaction with colleagues; this interaction is, I argue, based on sensemaking activity which occurs in a kinaesthetic loop that, while underpinned by creative empathy among musicians, draws on and is generated by auditory, visual and physical information virtually simultaneously. Which of these elements takes precedence was found in this study to be linked to the nature of the activity being undertaken.
Keywords: Orchestral musicians; Interpersonal relations; Sensemaking; Empathy